Customers’ Intention to Use Green Products: the Impact of Green Brand Dimensions and Green Perceived Value - Doszhanov Aibek; Ahmad Zainal Ariffin (SHS Web of Conferences, 2015)
This study aimed to identify the relationships between green brand dimension (green brand awareness, green brand image, and green brand trust), green perceived value and customer’s intention to use green products. Data was collected through structured survey questionnaire from 384 customers of three hypermarkets in Kuala-Lumpur. Data was analyzed based on multiple regression analysis. The results indicate that there are significant relationships between green brand awareness, green brand trust, green perceived value, and customer’s intention to use green products. However, green brand image was not found to have significant relationship with customer’s intention to use green products. The discussion presented suggestions for marketers and researchers interested in green branding.